Covering designs on 13 blocks revisited - Greig M.; Li P.C.; Van Rees G.H.J. (Utilitas Mathematica, 2006)
A (v, k, t)-Covering Design is a set of k-subsets of a set of v elements such that every set of t elements occurs in at least one block. The minimum number of blocks in any such design is denoted by C(v, k, t). We find all v and k so that C(v, k, 2) = 13 and give all the details and proofs. Further, we determine that C(28, 9, 2) = C(41, 13, 2) = 14.